Women writers of the new African diaspora : transnational negotiations and female agency - Uwakweh, Pauline Ada (Abingdon, Oxon ; New York, NY : Routledge, 2023)
"This book makes a significant addition to the field of literary criticism on African Diaspora literatures. In one volume, it brings together the novels of eight transnational African Diaspora women writers, Yaa Gyasi, Chika Unigwe, Chimamanda Adichie, Imbole Mbue, NoViolet Bulawayo, Aminatta Forna, Taiye Selasi, and Leila Aboulela, and positions them as chroniclers of African immigrant experiences. The book aims to inspire critical readings of these writers' works by revealing emerging trends in women's literature as they are being determined and redefined by immigration. As transnational subjects, the writers engage various meanings of mobility and exhibit innovative aesthetic styles; they create awareness on gender identities and transformations, constructions of home and belonging, as well as the politics of citizenship in the hostland. The book also highlights the import of reverse migrations and performance returns to the homeland as an expression of human desire for home and belonging, and taken as a whole, it enhances our understanding of how migration and transnational existence are (re)shaping immigrant subjects. This book will be of interest to scholars, students, and researchers of African Diaspora literatures and gender studies, who will find this book beneficial for investigating critical trends, approaches to transnational literature, and for comprehending the diasporic burdens that transnational immigrants bear"--
Introduction: Transnationalism and New African Diaspora Women Writers: An Overview -- Part I: Emigration: (En)gendering Transnationalism, Mobilities, and Politics of Representation -- Power of the Story: Mediating Africa's Diasporic Ruptures in Yaa Gyasi's Homegoing -- Specters of Slavery, Sites of Violence: Reading Chika Unigwe's On Black Sisters Street as a Neo-Slave Narrative -- Mobilities as Transnational Literary Aesthetics in Chimamanda Adichie's Americanah -- Part II: Negotiation: Transnational Identities, Home, and Intersectional Contexts -- Navigating the American Dream: Diaspora Families and Transnational Dilemmas in Mbolo Mbue's Behold the Dreamers -- 'The Home of Things Falling Apart': Narrating and Performing Home(land) in NoViolet Bulawayo's We Need New Names -- Enter the Afropolitan: Taiye Selasi's Cultural Significations in Ghana Must Go -- Narrative Identity in Ancestor Stones: Aminatta Forna's Postcolonial and Revisionist Discourse -- Gendered Journeys and Self-Discovery: The Transnational Context in Leila Aboulela's Bird Summons -- Part III: Retrurns: Reverse Migration, Ambivalent Returns, and Making Sense of Homeland -- Theorizing Homeland Returns in Transnational Women's Narratives -- Conclusion: Telescoping the Future of New African Diaspora Women's Literature.
Keywords: Fiction -- Women authors -- History and criticism; Fiction -- Black authors -- History and criticism; Fiction -- 21st century -- History and criticism; African diaspora in literature; Transnationalism in literature; Women, Black, in literature; Emigration and immigration in literature; Africa -- Emigration and immigration; LITERARY CRITICISM / African; LITERARY CRITICISM / Women Authors